Performance Goals and Indicators. Quick Turn Around (QTA) - Ahearn, Eileen M.; National Association of State Directors of Special Education, Alexandria, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
This brief paper summarizes a review of biennial performance reports filed by all 50 states concerning student performance goals and indicators required under the 1997 amendments to the Individuals with Disabilities Education Act. It notes that the state reports varied extensively in level of detail, clarity of content, and type of supporting materials included. States also differed substantially in the number, type, and level of abstraction of state goals for special education. Sixteen states use the same goals for students receiving special education as for other children. The most common areas addressed in goals were academic achievement, transition/postsecondary placements, teacher preparation/technical assistance, graduation rates, dropout rates, and communication/coordination with families/communities. The number of performance indicators that states reported using varied from 5 to 71. The content of performance indicators clustered around eight topics including: reaching graduation standards, inclusion in general education curriculum and/or assessments, improved dropout rates, and higher academic achievement. Suggestions are also offered to enhance the readability and usefulness of such reports including development of consensus definitions of "goals" and "performance indicators" and use of a consistent format for reporting of basic information. (DB)
Availability: National Association of State Directors of Special Education, 1800 Diagonal Road, Suite 320, Alexandria, VA 22314; Tel: 703-519-3800 (Voice); Fax: 703-519-3808; Web site: http://www.nasdse.org.
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC.
Contract Number: H159K70002.
ERIC Note: Produced by Project FORUM at NASDSE.
Policymakers.
May also be available online. Address as at 14/8/18
Keywords: Compliance (Legal); Disabilities; Educational Assessment; Educational Legislation; Elementary Secondary Education; Federal Legislation; National Surveys; State Standards; Student Educational Objectives; Individuals with Disabilities Educ Act Amend 199 -- Performance Indicators; Information Analyses; Reports, Evaluative